RNU12 inhibits gastric cancer progression via sponging miR-575 and targeting BLID - Wang, Shaoli; Zou, Changyan; Lin, Xinyi; Hu, Dan; Su, Ying; He, Huocong; Zheng, Xiongwei; Zhang, Lurong; Huang, Tao; Liao, Jin-rong; Lin, Xiandong (Scientific reports, 2023)
Gastric cancer (GC) is one of the major causes of cancer deaths with 5-year survival ratio of 20%. RNU12 is one of long noncoding RNAs (lncRNAs) regulating the tumor progression. However, how RNU12 affecting GC is not clear. qRT-PCR was utilized for determining the RNU12 expression in cell lines, 113 cases of paired gastric cancer (GC) and their adjacent normal gastric tissues. The biofunction alterations of RNU12 were assessed by its overexpression or knockdown in GC cells. MTT and cloning assay were assayed for the cell proliferation, the flow cytometry for the detection of cell cycle and the wound healing assay (WHA) and transwell invasion assay (TIA) for examining the migration and invasion of cells. The expressions of a set of genes related proliferation and migration were investigated with the Western Blotting (WB). RNA immunoprecipitation (RIP), biotinylated RNA pull-down and dual luciferase reporter tests were used to detect the interactions of RNU12 with miR-575/BLID. The in vivo proliferation and migration ability of RNU12 infected cells were determined in zebrafish system. This study revealed that RNU12 inhibited proliferation, invasion and metastasis by sponging of miR-575 and regulating the downstream BLID and modulated EMT of GC cells. The RNU12 /miR-575/BLID axis is likely to be the prognosis biomarkers and drug targets of GC.